Geroprotective and Radioprotective Activity of Quercetin, (-)-Epicatechin, and Ibuprofen in Drosophila melanogaster - Proshkina, Ekaterina; Lashmanova, Ekaterina; Dobrovolskaya, Eugenia; Zemskaya, Nadezhda; Kudryavtseva, Anna; Shaposhnikov, Mikhail; Moskalev, Alexey (Frontiers in Pharmacology, 2016)
The modulation of longevity genes and aging-associated signaling pathways using pharmacological agents is one of the potential ways to prolong the lifespan and increase the vitality of an organism. Phytochemicals flavonoids and non-steroidal anti-inflammatory drugs have a large potential as geroprotectors. The goal of the present study was to investigate the effects of long-term and short-term consumption of quercetin, (-)-epicatechin, and ibuprofen on the lifespan, resistance to stress factors (paraquat, hyperthermia, γ-radiation, and starvation), as well as age-dependent physiological parameters (locomotor activity and fecundity) of Drosophila melanogaster. The long-term treatment with quercetin and (-)-epicatechin didn’t change or decreased the lifespan of males and females. In contrast, the short-term treatment with flavonoids had a beneficial effect and stimulated the resistance to paraquat and acute γ-irradiation. The short-term ibuprofen consumption had a positive effect on the lifespan of females when it was carried out at the middle age (30-40 days), and to the survival of flies under conditions of oxidative and genotoxic stresses. However, it didn’t change the lifespan of males and females after the treatment during first 10 days of an imago life. Additionally, quercetin, (-)-epicatechin, and ibuprofen decreased the spontaneous locomotor activity of males, but had no effect of stimulated the physical activity and fecundity of females. Revealed quercetin, (-)-epicatechin, and ibuprofen activity can by associated with the stimulation of stress response mechanisms through the activation of pro-longevity pathways, or the induction of hormesis.